Peculiarities of bronchial asthma with obesity - Oxana Slaba; Walery Zukow (Kazimierz Wielki University, 2015)
Slaba Oxana, Zukow Walery. Peculiarities of bronchial asthma with obesity. Journal of Education, Health and Sport. 2015;5(2):117-124. ISSN 2391-8306. DOI: 10.5281/zenodo.15672 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A117-124 https://pbn.nauka.gov.pl/works/541144 http://dx.doi.org/10.5281/zenodo.15672 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015.   UDC: 616.248-036.001.33 Peculiarities of bronchial asthma with obesity   Oxana Slaba1, Walery Zukow2   1Danylo Halytsky Lviv National Medical University, Lviv, Ukraine 2Kazimierz Wielki University, Bydgoszcz, Poland   Corresponding Author: Oxana Slaba, Danylo Halytsky Lviv National Medical University e-mail: slabiyr@mail.ru   Abstract. In order to define the peculiarities of bronchial asthma with obesity there was carried out the analysis of the examination of 90 patients suffering from BA. The patients were divided in 3 groups: the first one consisted of 33 patients with normal body mass, the second one consisted of 29 patients with excessive body mass and the third one consisted of 28 patients with obesity. Bronchial asthma of the patients with obesity significantly more often was complicated by lung tissue pneumosclerosis and these patients more often were diagnosed the comorbid states - hypertensive heart disease and type 2 diabetes. The patients from group with obesity significantly rarely were diagnosed allergic rhinitis and eosinophilia. Within analysis of the respiratory functions it was detected that the patients with obesity and excessive body mass had more expressive restrictive obstructions than the patients with normal body mass. Group with obesity included more women whose disease in comparison to man part was significantly more often complicated by pulmonary insufficiency of the third degree and pulmonary emphysema. In comparison to women men with obesity more often were suffering from type 2 diabetes mellitus.   Key words: bronchial asthma, phenotype, obesity.